Tracking control of a flexible beam by nonlinear boundary feedback. (1995) - Guo, Bao-Zhu; Song, Qian
Abstract : This paper is concerned with tracking control of a dynamic model consisting of a flexible beam rotated by a motor in a horizontal plane at the one end and a tip body rigidly attached at the free end. The well-posedness of the closed loop systems considering the dissipative nonlinear boundary feedback is discussed and the asymptotic stability about difference energy of the hybrid system is also investigated.